Upaya dan Kendala dalam Memberikan Perlindungan Hukum Terhadap Anak Yang Menjadi Korban Kekerasan Seksual di Manggarai Barat - Rivaldus Ronjo; Rudepel Petrus Leo; Deddy R. Ch. Manafe (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this research is to analyze the efforts and obstacles in providing legal protection to children who are victims of sexual violence in West Manggarai. This research is an empirical juridical research in which this research was conducted at the Social Service of Women Empowerment and Protection of West Manggarai Regency, West Manggarai Resort Police, and West Manggarai Women and Children's Home. Data collection techniques used interviews and document/literature studies. The data used were primary data and secondary data. The results of the data processing were analyzed descriptively qualitative. The results of this study indicate that legal protection efforts against child victims of sexual violence in West Manggarai are providing legal assistance to children who are victims of violence, providing spiritual guidance to victims of sexual violence, providing health assistance to victims to check their health, providing safe houses or shelters, applying criminal sanctions for perpetrators. Obstacles in providing legal protection to child victims of sexual violence in West Manggarai are community factors, cultural factors, infrastructure factors, law enforcement factors.